Cognitive appraisals linking dispositional mindfulness to athletes' emotions: a multi-states theory approach - Robazza, Claudio; Vitali, Francesca; Bortoli, Laura; Ruiz, Montse C. (Frontiers in Sports and Active Living, 2024)
PurposeThe aim of the study was to examine the relationship between dispositional mindfulness, cognitive appraisals, emotions, and psychobiosocial experiences in athletes within the framework of multi-states (MuSt) theory.MethodA convenience sample of 334 Italian athletes (188 men and 146 women), aged 18–48 years (M = 24.77, SD = 7.26) and involved in individual or team sports, were recruited for the study. Athletes were assessed individually or in small groups before regular practice sessions.ResultsPath analysis showed positive indirect effects via challenge appraisal from mindful awareness and refocusing to excitement, happiness, and psychobiosocial experiences, and negative indirect effects to anxiety and dejection. Positive indirect effects were observed via threat appraisal from mindful awareness and refocusing to happiness and psychobiosocial experiences, and negative indirect effects to anxiety, dejection, and anger.ConclusionsThe results highlight the impact of mindful awareness, refocusing, and cognitive appraisals on athletes' emotional and psychobiosocial experiences. Overall findings support MuSt theoretical foundation and suggest that mindfulness may help athletes view challenges as opportunities to express their potential by triggering pleasant emotions and functional psychobiosocial experiences. From an applied perspective, the findings support the use of mindfulness practice in the development of programs to promote athletes' challenge appraisals, pleasant and functional emotional experiences, which may enhance their performance.